Authors' reply to the Letter to the Editor: Tissue factor and its procoagulant activity on cancer‐associated thromboembolism in pancreatic cancer. Issue 5 (24th March 2022) - Koizume, Shiro; Kobayashi, Satoshi; Ruf, Wolfram; Miyagi, Yohei
Abstract : Tissue factor‐procoagulant activity (TF‐PCA) on cells is modified by multiple molecular mechanisms of encryption and decryption. The risk of thrombosis is higher for patients with a high tissue factor antigen level at registration as this enables patient's blood more PCA‐high status before the onset of cancer‐associated thromboembolism (CAT). ELISA, including the Quantikine assay with validation as performed in our study, can contribute to more precise prediction of CAT.